Deteksi Dini & Edukasi Cerdik Terstruktur Untuk Pencegahan Sindrom Metabolik Pada Remaja Di Karawang - Nita Syamsiah; Uun Nurjanah; Sudiono (Yayasan Pemimpin Inovasi Science, 2025)
Metabolic syndrome is a collection of cardiovascular risk factors that include central obesity, hypertension, hyperglycemia, and dyslipidemia, which can lead to heart disease and type 2 diabetes. The prevalence of metabolic syndrome among adolescents shows an increasing trend, particularly due to changes in lifestyle and unhealthy dietary patterns. The objectives this programs is to prevent metabolic syndrome in adolescents through early detection and structured education using the CERDIK approach (C=Cek - Regular health Check-ups, E=Enyahkan - Avoiding cigarette smoke, R=Rajin aktifitas - Regular physical activity, D= Diet seimbang - Healthy diet with balanced calories, I= istirahat cukup - Adequate rest, and K=Kelola Stres - Stress management). This activity was carried out in several senior high schools and vocational schools (SMA/SMK) in Karawang Regency, involving students as the main targets. The methods used included health examinations, anthropometric measurements, and lifestyle surveys, followed by interactive education on healthy living behaviors. The expected outcomes of this program are to increase adolescents' awareness of the importance of early detection and the implementation of a healthy lifestyle to prevent the risk of metabolic syndrome from an early age. In addition, this program is also expected to reduce the prevalence of metabolic syndrome risk factors in the adolescent population in the region.